2007
DOI: 10.1093/brain/awm191
|View full text |Cite
|
Sign up to set email alerts
|

PIB is a non-specific imaging marker of amyloid-beta (A ) peptide-related cerebral amyloidosis

Abstract: The in vivo imaging probe [11C]-PIB (Pittsburgh Compound B, N-methyl[11C]2-(4'-methylaminophenyl-6-hydroxybenzathiazole) is under evaluation as a key imaging tool in Alzheimer's disease (AD) and to date has been assumed to bind with high affinity and specificity to the amyloid structures associated with classical plaques (CPs), one of the pathological hallmarks of the disease. However, no studies have systematically investigated PIB binding to human neuropathological brain specimens at the tracer concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
244
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(270 citation statements)
references
References 49 publications
22
244
0
4
Order By: Relevance
“…In the absence of congophilic angiopathy, perivascular accumulation of PiB has been previously reported as representing either a nonspecific interaction (27,28) or an artifact (28).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of congophilic angiopathy, perivascular accumulation of PiB has been previously reported as representing either a nonspecific interaction (27,28) or an artifact (28).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the histological hallmarks of AD pathology, comprising amyloid plaques and neurofibrillary tangles, are known to occur up to 10 to 20 years before the objective detection of cognitive decline [1]. Recently, positron emission tomography (PET) using Pittsburgh compound B (PiB) has been introduced as a diagnostic tool to detect cerebral amyloid in vivo [2][3][4][5][6][7][8]. The major disadvantages of PiB-PET are the need to use a radioactive tracer, the relative scarcity of institutions that can perform such scans because of the requirement for an onsite cyclotron, the inability to acquire anatomic and functional information in the brain during the same examination, and the greater chance of false positives, making interpretation of PiB-PET scans more difficult, especially in the elderly, which hampers the use of this method as a diagnostic tool in the elderly [9].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, on the basis of concentrations achieved during PET studies, cortical retention of 11 C-PIB has been shown to reflect Aβ load as opposed to Lewy bodies or tau pathology (Fodero-Tavoletti et al, 2007;Lockhart et al, 2007;Ikonomovic et al, 2008). In addition to accelerating current understanding of cerebral amyloidosis and advancing detection of AD pathology to an earlier stage (Klunk et al, 2004;Mintun et al, 2006;Rowe et al, 2007;Cohen et al, 2012), 11 C-PIB has contributed to improvements in the differential diagnosis of neurodegenerative diseases (Ng et al, 2007;Rabinovici et al, 2007;Rowe et al, 2007).…”
Section: First Generation Of Amyloid Probes: 11 C Pittsburgh Compound Bmentioning
confidence: 99%